2018
DOI: 10.1111/imr.12655
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid metabolism in CD8+ T cell memory: Challenging current concepts

Abstract: Fatty acid metabolism in CD8+ T cell memory CD8+ T cells are key members of the adaptive immune response against infections and cancer. As we discuss in this review, these cells can present diverse metabolic requirements, which have been intensely studied during the past few years. Our current understanding suggests that aerobic glycolysis is a hallmark of activated CD8+ T cells, while naïve and memory (Tmem) cells often rely on oxidative phosphorylation, and thus mitochondrial metabolism is a crucial determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 200 publications
(534 reference statements)
4
93
0
Order By: Relevance
“…Thus, T cells exiting quiescence increase anabolic pathways and their intermediates can be used for synthesis or enter the TCA cycle to fuel mitochondrial OXPHOS(Figure 1 bottom). In contrast, Treg and Tm use OXPHOS and FAO, with emerging reports indicating T cells are more metabolically flexible than previously thought 271. These findings indicate distinct T cell subtypes use different metabolic pathways.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, T cells exiting quiescence increase anabolic pathways and their intermediates can be used for synthesis or enter the TCA cycle to fuel mitochondrial OXPHOS(Figure 1 bottom). In contrast, Treg and Tm use OXPHOS and FAO, with emerging reports indicating T cells are more metabolically flexible than previously thought 271. These findings indicate distinct T cell subtypes use different metabolic pathways.…”
mentioning
confidence: 74%
“…Several studies of mitochondrial dynamics indicate FAO is a pivotal regulator of Tm fate. 271 Antigen-specific CD8 Tm development is dependent on TRAF6-regulated lipid metabolism and TRAF6 deficiency resulted in defective AMPK activation and diminished FAO. 279 Furthermore, mice with T cells lacking TRAF6 have excessive cytokine production, suggestive of an abnormal Th effector response.…”
Section: T Cell Metabolism In Influenza Infectionmentioning
confidence: 99%
“…The importance of LC‐FAO for memory T‐cell development, has recently been challenged by a study using mice with a T cell‐specific deletion of CPT1a . Furthermore, the use of etomoxir, a CPT1 inhibitor, used extensively in studies assessing LC‐FAO, was demonstrated in multiple contexts to have off‐target effects that could cloud the interpretation of findings relying on etomoxir to inhibit CPT1a . In contrast to previous studies that used either genetic overexpression, hairpin or siRNA‐mediated knockdown, or drug inhibition of CPT1a, Raud et al .…”
Section: Substrate Utilization In Memory T Cellsmentioning
confidence: 99%
“…61 Furthermore, the use of etomoxir, a CPT1 inhibitor, used extensively in studies assessing LC-FAO, was demonstrated in multiple contexts to have off-target effects that could cloud the interpretation of findings relying on etomoxir to inhibit CPT1a. 61,65,66 In contrast to previous studies that used either genetic overexpression, hairpin or siRNA-mediated knockdown, or drug inhibition of CPT1a, Raud et al 61 used a Cpt1aflox-CD4 Cre conditional deletion to specifically delete CPT1a in T cells. They provide convincing evidence that CD8 + T cells from these mice survive and establish a secondary effector response to L. monocytogenes infection thus calling into question the requirement for CPT1a in memory T-cell function.…”
Section: Substrate Utilization In Memory T Cellsmentioning
confidence: 99%
“…Key substrates for the TCA cycle can be derived from fatty acids and amino acids. Specifically, resting T cells can use FAO (beta oxidation) to fuel the TCA cycle (Figure ). Fatty acids are transported into the mitochondrial matrix by a complex containing carnitine palmitoyltransferase Ia, where they undergo FAO to generate acetyl‐CoA that can enter the TCA cycle.…”
Section: The Fundamentals Of T Cell Metabolismmentioning
confidence: 99%